2022
DOI: 10.3390/math10030342
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Natural Convection of Power Law Fluid in a Square Cavity Fitted with a Uniformly Heated T-Fin

Abstract: Flow of a liquid in an enclosure with heat transfer has drawn special focus of researchers due to the abundant thermal engineering applications. So, the aim of present communication is to explore thermal characteristics of natural convective power-law liquid flow in a square enclosure rooted with a T-shaped fin. The formulation of the problem is executed in the form of partial differential expressions by incorporating the rheological relation of the power-law fluid. The lower wall of the enclosure along with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The governing equations for the two-dimensional steady flow following the invocation of the equations that govern the steady two-dimensional flow, considering the Boussinesq approximation and neglecting radiation and viscous dissipation, can be formulated in the following manner [6,33,[39][40][41][42]: Continuity equation:…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The governing equations for the two-dimensional steady flow following the invocation of the equations that govern the steady two-dimensional flow, considering the Boussinesq approximation and neglecting radiation and viscous dissipation, can be formulated in the following manner [6,33,[39][40][41][42]: Continuity equation:…”
Section: Governing Equationsmentioning
confidence: 99%
“…Turkyilmazoglu [32] studied nonuniform heating in free convection and found the best heat deletion rate close to the top wall of a cavity. Bilal et al [33] studied the power law fluid in a square cavity and found that heat conduction rises as the Rayleigh number increases, driven by the generation of temperature variations within the fluid domain. Sondur et al [34] performed a benchmark simulation on fluid flow inside a square cavity and they showed that the most accurate results were found for the steady flow solver Open FOAM which took a comparatively short time.…”
Section: Introductionmentioning
confidence: 99%
“…The illustration in Figure 1 depicts the physical layout of the problem. Considering the above assumptions, we utilize the following governing equations to represent the flow phenomenon [38][39][40][41] ∂u ∂x…”
Section: Mathematical Modelmentioning
confidence: 99%
“…They concluded that heat transfer rate between PCM and HTF has been enhanced significantly because of extended surface of vertical fins. Use of fins with PCMs in electronics is numerically investigated by Bilal, Khan, et al (2022b), Lacroix andBenmadda (1997), andNayak et al (2006) and it is found that the rate of heat transfer is enhanced up to a certain number of fins. Other than number of fins, fins geometry is also effective in heat transfer rate enhancement, such as rod-type fins.…”
Section: Extended Surfacesmentioning
confidence: 99%